Mechanical Properties of Polymethyl Methacrylate as Denture Base Material: Heat-Polymerized vs. 3D-Printed—Systematic Review and Meta-Analysis of In Vitro Studies - Cláudia Lourinho; Helena Salgado; André Correia; Patrícia Fonseca (Biomedicines, 2022)
The synergy between dentistry and informatics has allowed the emergence of new technologies, specifically 3D printing, which has led to the development of new materials. The aim of this research was to compare the mechanical properties of dental base resins for 3D printing with conventional ones. This systematic review was developed using the PRISMA guidelines, and the electronic literature search was performed with the PubMed/MEDLINE, Web of Science—MEDLINE and EMBASE databases, until 30 April 2022. Two researchers selected the studies independently, and thus eight articles were found eligible for analysis. A meta-analysis was developed to estimate flexural strength. The Cohen’s kappa corresponding to this review was 1.00, and the risk assessment was considered low for the included studies. The 3D printing resin presented lower values of flexural strength and hardness compared with the heat-cured resin. Regarding impact strength, a lower value was recorded for the heat-cured resin compared with the 3D printing resin. Three-dimensional printing resins are viable materials for making prosthetic bases but need further clinical research.